Super High Frequency Events: A New Class of Events Recorded by the InSight Seismometers on Mars. Issue 2 (24th February 2021) - Dahmen, Nikolaj L.; Clinton, John F.; Ceylan, Savas; van Driel, Martin; Giardini, Domenico; Khan, Amir; Stähler, Simon C.; Böse, Maren; Charalambous, Constantinos; Horleston, Anna; Kawamura, Taichi; Orhand‐Mainsant, Guenolé; et al.
Abstract: We present a new class of seismic signals that are recorded by the seismometer placed on the surface of Mars as part of the NASA InSight mission. The signals, termed super high frequency (SF) events, are of short duration (∼20 s), are often similar in amplitude, and feature high‐frequency energy between ∼5 and 30 Hz that is dominant on the horizontal components. For detection and characterization of SF events, we employ the available continuous 20 samples per second (sps) data from the Very Broadband instrument. Due to bandwidth limitations, 100 sps data from the short‐period sensor are only partially obtainable, but they aid in analysis of the frequency content above 10 Hz and in distinguishing the events from high‐frequency noise. From June 2019 to May 2020, 780 SF events have been detected. The events observed occur in repeatable patterns that last for weeks. Initially, the SF events were clustered in the hours before sunset, but more recently, they have been distributed across the evening period. Based on template matching techniques, we have identified 16 distinct families that generally follow the temporal clusters. A thermal origin of these events is suggested, since the majority of the events fall within a ±2 h time window around sunset with extreme temperature changes. The SF events have similarities with thermal events observed on the lunar surface from data collected during the Apollo missions. Plain Language Summary: The seismometers on Mars are recording high‐frequency signals of short duration. Seven hundred and eighty of these events have been found so far, that can be categorized into families with comparable signal shape. Each family repeats for a limited number of days at similar times of the day. At first, they occurred at or shortly before sunset, but more recently they are being observed later in the Martian evening. We infer these signals originate from close to the lander but not the lander itself, and may be related to thermal cracking, like the lunar thermal events observed during the Apollo missions. Key Points: Super high frequency events are a class of signals observed by the InSight seismometer on Mars Seven hundred and eighty events have been observed, typically lasting 20 s with energy mainly on horizontal components between 5 and 30 Hz Events appear in clusters and are likely associated with local thermal sources similar to observations on the Moon